2021
DOI: 10.1002/ptr.7293
|View full text |Cite
|
Sign up to set email alerts
|

Eleutheroside B‐loaded poly (lactic‐co‐glycolic acid) nanoparticles protect against renal fibrosis via Smad3‐dependent mechanism

Abstract: Although renal fibrosis is a common complication of chronic kidney disease (CKD), effective options for its treatment are currently limited. In this study, we evaluated the renal protective effect and possible mechanism of eleutheroside B. In order to solve the allergic reactions, side effects, and low oral bioavailability of eleutheroside B, we successfully prepared PLGA (poly [lactic-co-glycolic acid])eleutheroside B nanoparticles (NPs) with the diameter of about 128 nm. In vitro and in vivo results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Eleutheroside B was shown to bind to Smad3 molecular docking studies, resulting in a significant decrease in phosphorylated Smad3 (p-Smad3) expression. Eleutheroside B's fibrotic protective effect in HK2 cells was undone by silencing Smad3 [24].…”
Section: Resultsmentioning
confidence: 99%
“…Eleutheroside B was shown to bind to Smad3 molecular docking studies, resulting in a significant decrease in phosphorylated Smad3 (p-Smad3) expression. Eleutheroside B's fibrotic protective effect in HK2 cells was undone by silencing Smad3 [24].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have employed PLGA nanoparticles for eleutheroside B delivery and enhanced eleutheroside B bioavailability, with small animal imaging revealing that eleutheroside B-PLGA nanoparticles can selectively accumulate in mice kidneys for up to 7 days. 437 …”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“…The authors, however, concluded that the membrane replacement did not contribute to adversity for patients undergoing haemodialysis. 71,72 In other reported studies, further fabrication of cellulose into cellulose triacetate 73 or cellulose diacetate 74 reduced platelet activation, making it closer to the commercial dialyser membrane properties in terms of biocompatibility for a more feasible product.…”
Section: Polymers In Kidney Tissue Engineeringmentioning
confidence: 99%
“…It is widely used as a drug vehicle for its tailorable erosion capability, 70 which includes research to treat kidney fibrosis. 71,72…”
Section: Polymers In Kidney Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation